2020
DOI: 10.1177/1526602820918875
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Endovascular Aneurysm Repair Using the Anaconda Stent-Graft

Abstract: Purpose: To report outcomes of elective endovascular aneurysm repair (EVAR) using the Anaconda stent-graft in a tertiary vascular center. Materials and Methods: A retrospective study was conducted of 271 patients (mean age 71.5 years; 260 men) who underwent elective EVAR for abdominal aortic aneurysm using the Anaconda stent-graft from January 2006 to January 2017. Median aneurysm diameter was 58 mm (range 50–90). All patients were anatomically suitable for EVAR according to the 2003 version of the instruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…43 Possibly related to this, the second-generation infrarenal Anaconda™ endograft was prone to limb occlusion, thought to be related to compression of the limbs due to a mismatch between the J o u r n a l P r e -p r o o f smaller main body and relatively large limb diameters. 17,44 To allow for easier limb size selection, the third-generation graft (ONE-LOCK™) was launched in 2011, with a standardized proximal docking zone and different types of distal limb configurations (straight, flared or tapered). 17 Most of the reported experience with the Anaconda™ endograft comes from secondgeneration devices.…”
Section: Discussionmentioning
confidence: 99%
“…43 Possibly related to this, the second-generation infrarenal Anaconda™ endograft was prone to limb occlusion, thought to be related to compression of the limbs due to a mismatch between the J o u r n a l P r e -p r o o f smaller main body and relatively large limb diameters. 17,44 To allow for easier limb size selection, the third-generation graft (ONE-LOCK™) was launched in 2011, with a standardized proximal docking zone and different types of distal limb configurations (straight, flared or tapered). 17 Most of the reported experience with the Anaconda™ endograft comes from secondgeneration devices.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 A summary of the finding in this subsection can be found in Table 1 alongside results from additional Anaconda™ studies [26][27][28][29][30][31] as well as studies investigating Zenith [32][33][34][35] (to be discussed in the section 'Competitor devices'). Saratzis et al 12 Anaconda™ N = 51 16 0 3.9 Stella et al 13 Anaconda™ N = 100 23 3.3 3.3 Rödel et al 14 Anaconda™ N = 61 24 3.3 9.8 Freyrie et al 18 Anaconda™ N = 787 − 1.2 − Karkos et al 15 Anaconda™ N = 68 29 0 20 Rödel et al 24 Anaconda™ N = 36 40 0 22 Rolls et al 25 Anaconda™ N = 13 12 0 − Freyrie et al 17 Anaconda™ N = 177 33 1.1 3.6 Dijkstra et al 16 Anaconda™ N = 25 -0 2 0 Gallitto et al 26 Anaconda™ N = 26 12 7.7 − Shahverdyan et al 27 Anaconda™ N = 48 24 4 6 Kotelis et al 28 Anaconda™ N = 39 − 8 1 8 Colgan et al 29 Anaconda™ N = 101 − 3 − Midy et al 30 Anaconda™ N = 86 24 7 21.7 de Niet et al 31 Anaconda™ N = 29 -14 19 Midy et al 19 Anaconda™ N = 176 -1.7 5.1 Tigkiropolous et al 20 Anaconda™ N = 271 72 1.1 21 de Niet et al 23 Anaconda™ N = 335 − 4.2 15.8 Pini et al 21 Anaconda™ N = 127 21 4 9 Isernia et al 22 Anaconda™ N = 260 54 0.8 5.2 Verzini et al 32 Zenith N = 610 99 0.8 7.2 Vaaramaki et al 33 Zenith N = 282 − 1.8 7 Kawamata et al 34 Zenith N = 95 50 0 23.2 Oderich et al 35 Zenith N = 67 59 1.5 10.4…”
Section: Mortality and Survivalmentioning
confidence: 99%
“…The authors reported freedom from reintervention and open conversion rates to be 95.6% and 99.2% at 1 year, 87.0% and 96.9% at 5 years, 77.4% and 94.0% at 10 years, and finally, 77.4% and 94.0% at 13 years, respectively. The Bologna group also found excellent freedom from 39 Anaconda™ N = 14 6 0 Saratzis et al 12 Anaconda™ N = 51 16 9.8 Stella et al 13 Anaconda™ N = 100 23 1 Rödel et al 14 Anaconda™ N = 61 24 14.8 Freyrie et al 18 Anaconda™ N = 787 − 12 Karkos et al 15 Anaconda™ N = 68 29 17.5 Rödel et al 24 Anaconda™ N = 36 40 11 Rolls et al 25 Anaconda™ N = 13 12 0 Freyrie et al 17 Anaconda™ N = 177 33 14.1 Dijkstra et al 16 Anaconda™ N = 25 − 0 Gallitto et al 26 Anaconda™ N = 26 12 11.5 Shahverdyan et al 27 Anaconda™ N = 48 24 21 Kotelis et al 28 Anaconda™ N = 39 − 5 Colgan et al 29 Anaconda™ N = 101 − 14.9 Midy et al 30 Anaconda™ N = 86 24 15.5 de Niet et al 31 Anaconda™ N = 29 − 10.3 Midy et al 19 Anaconda™ N = 176 − 27.2 Tigkiropolous et al 20 Anaconda™ N = 271 72 5 de Niet et al 23 Anaconda™ N = 335 − 7.4 Pini et al 21 Anaconda™ N = 127 21 4 Isernia et al 22 Anaconda™ N = 260 54 15 Verzini et al 32 Zenith N = 610 99 22.9 Vaaramaki et al 33 Zenith N = 282 − 41 Kawamata et al 34 Zenith N = 95 50 21.1 Oderich et al 35 Zenith N = 67 59 3 reintervention rates at 12-, 24-and 36-months which were 94%, 92% and 85%, respectively. 17 By 2 years follow-up, Rödel et al 14 and Stella et al 13 reported similar freedom from reintervention rates of 85.2% and 88.8%, respectively, and 100% freedom from endograft migration in both.…”
Section: Reintervention Conversion Endograft Migration Competitor Res...mentioning
confidence: 99%
See 2 more Smart Citations